MOTIVASI INDONESIA BEKERJASAMA DENGAN PAKISTAN DALAM BIDANG PERTAHANAN - Gothman Tambunan; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is to explain why Indonesia cooperate in defense with Pakistan in order to improve defense and security. Indonesia has a very large area, both land, air and sea, and flanked by two oceans and two continents. Many countries with great power in the world have influence in the region. Thus, Indonesia's security level must be strong to maintain the sovereignty of its territory.The perspective used in this study is realism with Donald E. Nuechterlein national interest theory. The data used is secondary data, which comes from books, journals, mass media and internet websites. Research method is library research by analyzing data from above sources.The results of this study show that the national interests of Indonesia are achieved in defense cooperation with Pakistan. Improving the quality of army personnel, improved relations with Pakistan especially in the defense sector.Keywords : defence cooperate, national interest, memorandum of understading